Volumetric Differences in the Suprafascial and Subfascial Compartments of Patients with Secondary Unilateral Lower Limb Lymphedema. Issue 6 (June 2020) - Chu, Sung-Yu; Wang, Stewart C.; Chan, Wen-Hui; Wang, Nicholas; Huang, Yen-Ling; Cheng, Ming-Huei; Cederna, Paul Stephen
Abstract : Background: The subfascial compartment (deep to the deep fascia) in extremity lymphedema has not been evaluated. This study investigated the volumetric differences between the suprafascial and subfascial compartments of patients with unilateral lower extremity lymphedema. Methods: Thirty-two female patients with unilateral lower extremity lymphedema were enrolled, with eight patients in each of Cheng lymphedema grades I to IV. The volumes of the suprafascial and subfascial compartments were calculated after manually drawing the region of interest on computed tomographic images. The volumetric differences and their ratios in the suprafascial and subfascial compartments between each patient's bilateral limbs were compared. Results: The volume of the lymphedematous limbs (9647 ml) was significantly greater than the volume of unaffected limbs (6906 ml), with a median volumetric difference of 2097 ml (30.6 percent) ( p < 0.01). The median suprafascial compartment volumetric difference was 1887 ml (56.6 percent) and the subfascial compartment volumetric difference was 208 ml (4.7 percent) ( p < 0.01). The median volumetric difference ratio of the thigh and lower leg was 24.6 percent and 40.6 percent, respectively. The median volumetric differences in Cheng lymphedema grades I to IV were 1012, 1787, 2434, and 4107 ml, respectively, which were statistically significant among the four Cheng lymphedema grades using the Kruskal-Wallis test ( p < 0.01). Conclusions: The volumetric differences in the lymphedematous limb were statistically significantly greater than in the unaffected limb, including both suprafascial and subfascial compartments. The volumetric differences are consistent with the Cheng lymphedema grading system as a reliable indicator of unilateral extremity lymphedema. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV.